Tracing Your Family History : The Complete Guide to Locating Your Ancestors and Finding Out Where You Came From - Hull, Lise (London Reader's Digest Book, 2006)
A comprehensive guide to researching family histories and ancestors; and provides information on accessing various online sources, filing and storing material, and locating documents.
Include Color Illustration and Index
Keywords: United States -- Great Britain -- Genealogy